An Overview of the Karst Areas in British Columbia, Canada - Stokes, Tim R.; Griffiths, Paul A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2019)
Karst is a three-dimensional landscape that occurs in soluble bedrock (typically limestone, marble, dolostone, gypsum or halite) and is defined by a solutionally weathered surface, a subsurface drainage system (where conduit-flow dominates), and underground openings and caves. Karst can host unique flora and subsurface fauna, as well as a wide range of other scientific, recreational and cultural values. Karst and potential karst areas underlie approximately 10% of British Columbia (BC), but the distribution and extent of this landscape has yet to be fully explored and delineated. Some of the most extensive and well-developed karst areas occur within the forestedlimestone areas of coastal BC, such as on Vancouver Island and Haida Gwaii, where numerous surface karst features and caves are known. Karst in the interior plateau regions of British Columbia is less well known, being in part covered by thick deposits of glacial materials. Alpine karst regions are most apparent in the Rocky Mountains where there are limestone plateaus, karst drainages and cave systems that have close connections to past and present glacial systems. Mapping of karst is a critical component for any land-use or resource development activity in all regions of British Columbia, as the environmental impacts on karst and its associated values are potentially significant. The regional distribution of karst in BC is not well mapped, with only an office-based reconnaissance karst potential map (1:250,000-scale) and a related database completed in 1999. A renewed effort should now be made to better map karst across British Columbia using digital bedrock mapping data released in 2017, combined with more recent satellite imagery and improved field knowledge.